Teaching in the online classroom : surviving and thriving in the new normal - Lemov, Doug (a Wiley brand : Jossey-Bass, 2020)
Although the transition to online education is happening more abruptly than anyone anticipated, technology-supported teaching may be here to stay. This guide explores the challenges involved in online teaching and guides educators and administrators to identify and understand best practices. It is a valuable tool to help you and your students succeed in synchronous and asynchronous settings this school year and beyond. Learn strategies for engaging students more fully online. Find new techniques to assess student progress from afar. Discover tools for building online classroom culture, combating online distractions, and more"-- Provided by publisher
Keywords: Computer-assisted instruction; Education; Educational technology